Flow Control Mechanism of Blade Tip Bionic Grooves and Their Influence on Aerodynamic Performance and Noise of Multi-Blade Centrifugal Fan - Ziqian Xu (Energies, 2022)
To improve the aerodynamic performance and reduce the noise of multi-blade centrifugal fans used in air conditioners, a bionic groove structure was introduced into the blade tip design, inspired by the drag reduction characteristics of mantis shrimp. In this paper, the numerical method was used to investigate the effects of a blade tip bionic groove on the aerodynamic performance and noise characteristics of a multi-blade centrifugal fan. Firstly, the basic design parameters, such as groove width, groove depth, groove center distance, and groove number, were selected to define the shape of the blade tip bionic groove. Then, the effect of the design parameters on the aerodynamic performance of the multi-blade centrifugal fan was studied. Finally, the multi-blade centrifugal fan models with different groove shapes, such as rectangular bionic grooves, circular bionic grooves, and triangular bionic grooves, were established to compare the influence of blade tip groove structures on the aerodynamic performance of the multi-blade centrifugal fan. Through analysis of the aerodynamic performance and noise characteristics of the multi-blade centrifugal fan and the flow fields in the fan impeller, the flow control mechanism of the blade tip bionic groove was revealed. The results showed that the triangular bionic groove on the blade tip had a certain noise reduction effect, although the structural parameters of the bionic groove had little effect on the aerodynamic performance of the multi-blade centrifugal fan. This is because the triangular bionic groove structure can effectively inhibit the vortex shedding at the trailing edge of blade and reduce the flow separation in the impeller passages. As a result, the velocity distribution at the impeller tip became more uniform and the intensity of the tip vortex and the shedding vortex was weakened. Correspondingly, the noise of multi-blade centrifugal fan was also reduced to some extent.